Attention to Stem Cell Research in Japanese Mass Media: Twenty-Year Macrotrends and the Gap between Media Attention and Ethical, Legal, and Social Issues. Issue 3 (1st September 2016) - Shineha, Ryuma
Abstract : This article aims to describe time-lined changes in the topics and framings of stem cell research (SCR) and regenerative medicine (RM) in Japanese mass media after the 1990s. Seventy-four hundred news articles were collected and analyzed for co-word network structures. Network changes concerning keywords such as ethics ( rinri 倫理), egg ( ranshi 卵子), and guidelines ( shishin 指針) were found to be features of Japanese media discourse. In particular, after the appearance of human induced pluripotent stem cells (iPSCs) in 2007, there was a rapid decrease in the number and variety of connections with keywords related to ethical aspects. This result reveals changes in the position and treatment of the ethical aspects of SCR, indicating a peripheralization of ethical, legal, and social issues (ELSI) in current Japanese media. The gap between the actual status of ELSI and media attention will seriously affect the agenda building and frame building of the public.